PENYULUHAN TENTANG HIV/AIDS PADA LELAKI BERISIKO TINGGI DI BUKIT MARAJA - Dian Permata Nasution; Marolop Parlindungan Napitu; Jumadiah Wardati; Jesicca Hasibuan (Nusantara Hasana Journal, 2025)
This community service report presents an HIV/AIDS counseling and prevention initiative targeting high-risk men in Bukit Maraja. The activities were carried out by implementing key strategies—diagnose, treat, prevent, and respond—aligned with the Ending the HIV Epidemic (EHE) initiative. In this project, motivational interviewing techniques and peer outreach approaches were utilized to increase HIV testing uptake and the return of test results. The counseling was delivered by intensively trained field staff in collaboration with various stakeholders, ensuring effective targeting of high-risk groups. The program outcomes showed significant improvements in HIV knowledge, testing rates, and awareness about available services. These findings highlight the importance of community empowerment and persistent support to overcome structural barriers in the access to HIV/AIDS services